2013
DOI: 10.1111/1475-6773.12115
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Evidence‐Based Employment Services in Specialty Mental Health

Abstract: Objective Study a quality improvement approach for implementing evidence-based employment services at specialty mental health clinics. Data Sources/Study Setting Semistructured interviews with clinicians and administrators before, during, and after implementation. Qualitative field notes, structured baseline and follow-up interviews with patients, semistructured interviews with patients after implementation, and administrative data. Study Design Site-level controlled trial at four implementation and four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Weight outcomes were signifi cantly improved at all sites by study end (Cohen, Chinman, Hamilton, Whelan, & Young, 2013 ;Hamilton et al, 2013 ). In comparison to the prior EQUIP pilot, this was larger in scope and more sophisticated in its evaluation.…”
Section: Case Study: Improving the Quality Of Care For Schizophreniamentioning
confidence: 82%
See 1 more Smart Citation
“…Weight outcomes were signifi cantly improved at all sites by study end (Cohen, Chinman, Hamilton, Whelan, & Young, 2013 ;Hamilton et al, 2013 ). In comparison to the prior EQUIP pilot, this was larger in scope and more sophisticated in its evaluation.…”
Section: Case Study: Improving the Quality Of Care For Schizophreniamentioning
confidence: 82%
“…Some have been highly effective, while others have been frustrated, mostly by organizational or fi nancial constraints (Drake et al, 2013;Frey et al, 2008Frey et al, , 2011Hamilton et al, 2013 ;McHugo et al, 2007 ). This consists of assistance obtaining and maintaining competitive employment.…”
Section: Quality Improvement For Evidence-based Practicesmentioning
confidence: 99%
“…Improvement in the distal outcome of competitive employment was limited to one site that had a high level of treatment fi delity. Weight outcomes were signifi cantly improved at all sites by study end (Cohen, Chinman, Hamilton, Whelan, & Young, 2013 ;Hamilton et al, 2013 ). Process evaluations indicated that the PAS was useful and feasible in usual care settings (Cohen, Chinman et al, 2013 ).…”
Section: Case Study: Improving the Quality Of Care For Schizophreniamentioning
confidence: 98%
“…There have been numerous efforts to engage in QI focused on supported employment. Some have been highly effective, while others have been frustrated, mostly by organizational or fi nancial constraints (Drake et al, 2013;Frey et al, 2008Frey et al, , 2011Hamilton et al, 2013 ;McHugo et al, 2007 ).…”
Section: Quality Improvement For Evidence-based Practicesmentioning
confidence: 99%
“…Hamilton et al. () illustrate the use of mixed methods in quality improvement research using a convergent design within an intervention framework. The results are a great example of using a contiguous narrative to present their key findings for care of veterans with mental health problems.…”
Section: The Papersmentioning
confidence: 99%